Metaphor: window to the native speakers' mind - Rashid Ali, Farrah Diebaa (Universiti Teknologi MARA, 2014)
This paper looks at the importance of learning and understanding metaphor among second language learners. It begins with a brief overview of the Sapir-Whorf linguistic relativity theory. It provides further discussion of Lakoff and Johnson (1980), Andrew Goatly (2000) and CharterisBlack’s (2011) framework on conceptual metaphor. Discussion of these theories will highlight the critical roles played by metaphor in everyday basic communication to convey complex idea and persuasion. Failure to recognize and understand metaphor will be detrimental to L2 learners’ proficiency and hinder their ability to communicate effectively. L2 learners may also overlook important information or overemphasize trivia. The ability to recognize and understand metaphor will help L2 learners communicate effectively with the native speakers and this will provides first-hand second language cultural experience to the learners.